Role of Panchakarma in Gridhrasi with special reference to Peroneal Neuropathy - Jukur Rajesh; Tejali Rohidas; Ananta S Desai (AYUSHDHARA, 2024)
The collective meaning of Vatavyadhi indicates the specific disorder occurring due to Vata Dosha. Wherever, Vata Dosha get vitiated it first enters in all Srotas of the body and then creates different types of Vata Vyadhi describe in Classical Ayurvedic text. Objective: The aim of this study was to access the efficacy of Ayurvedic management including Shodhan and Shaman Chikitsa in Gridhrasi. Material and Method: A 45 year old male patient who is not a known case of diabetic mellitus and hypertension came to hospital with complain of pain low back radiating to bilateral lower limb (Rt.>Lt.) since 2 months associated with weakness, stiffness, heaviness of right lower limb and dragging type of gait due to right foot drop since 2 weeks which was diagnosed with Vata- Kahaja Gridhrasi and was treated with Dashamoola and Mahamanjistadi Qwatha Seka for 7 days, Churna Basti for 3 days, Patra Pinda Sweda for 7 days, Mustadhi Yapana Basti for 9 days, Shastika Shali Pinda Sweda for 15 days. Result: After completion of one month of total treatment, the patient as found significant relief in the back pain, numbness, heaviness, improvement in gait and gain in strength in bilateral lower limb Conclusion: Gridhrasi can occur due to Abhigataja and Dhatuksaya where Vatakaphaja Lakshana were predominantly seen in the case and treated with Seka, Basti, different types of Sweda. To combat the disease in minimum duration we have used multi treatment approach to get synergistic effect.